Investigation of acoustic field near to elastic thin plate using integral method - Токарев, В.І.; Запорожець, О.І. (Proceedings of National Aviation University (archive), 2004)
Investigation of acoustic field near to elastic thin plate using integral method The influence of boundary conditions on sound wave propagation, radiation and transmission through thin elastic plate is investigated. Necessary for that numerical model was found using the Helmholtz equation and equation of oscilated plate by means of integral formulation of the solution for acoustic fields near to elastic thin plate and for bending waves of small amplitudes.